Vibrational Probes of Molybdenum Cofactor–Protein Interactions in Xanthine Dehydrogenase - Dong, Chao (Inorg Chem, 2017)
The pyranopterin dithiolene (PDT) ligand is an integral component of the molybdenum cofactor (Moco) found in all molybdoenzymes with the sole exception of nitrogenase. However, the roles of the PDT in catalysis are still unknown. The PDT is believed to be bound to the proteins by an extensive hydrogen bonding network, and it has been suggested that these interactions may function to fine-tune Moco for electron and atom transfer reactivity in catalysis. Here, we use resonance Raman (rR) spectroscopy to probe Moco-protein interactions using heavy atom congeners of lumazine; molecules that bind tightly to both wt-XDH and its Q102G and Q197A variants following enzymatic hydroxylation to the corresponding violapterin product molecules. The resulting enzyme-product complexes possess intense NIR absorption, allowing high quality rR spectra to be collected on wt-XDH and the Q102G and Q197A variants. Small negative frequency shifts relative to wt-XDH are observed for low-frequency Moco vibrational. These results are interpreted in the context of weak hydrogen bonding and/or electrostatic interactions between Q102 and the −NH(2) terminus of the PDT, and between Q197 and the terminal oxo of the Mo≡O group. The Q102A, Q102G, and Q197A, Q197E variants do not appreciably affect the kinetic parameters k(red), and k(red)/K(D), indicating a primary role for these glutamine residues is to stabilize and coordinate Moco in the active site of XO family enzymes, but not directly affect catalytic throughput. Raman frequency shifts between wt XDH and its Q102A variant suggest the changes in the electron density at the Mo ion that accompany Mo oxidation during electron transfer regeneration of the catalytically competent active site are manifest in distortions at the distant PDT amino terminus. This implies a primary role for the PDT as a conduit for facilitating enzymatic electron transfer reactivity in xanthine oxidase family enzymes.